Exploring The Potential of Microlearning for Toefl Ibt Preparation Among High School Students - Faizal Rizky, Muhammad; H, Nurhikmah; Febriati, Farida (Universitas Negeri Makassar, 2023)
The aim of this needs analysis is to investigate the potential of microlearning as a learning approach to prepare high school students for the TOEFL iBT. Microlearning is an instructional method that involves brief participation in an activity that is intended to yield a specific result. While prior research has shown its benefits in encouraging independent learning, reducing mental fatigue, and preventing demotivation and cognitive impairments, most studies have focused on adult learners, with only a small fraction conducted in high school settings. In Indonesia, certificates of English aptitude tests, such as TOEFL iBT, are necessary for higher education and job applications. However, the topic and skills are rarely discussed in schools, resulting in many high school graduates being unprepared for the exam. Typically, students resort to private institutions or tutors to acquire the necessary skills, but the associated costs and time commitment can be discouraging. Therefore, it is essential to examine the perceived importance of TOEFL iBT, learning difficulties, and learning preferences. The findings will inform recommendations on integrating microlearning into the existing educational framework. Future studies should explore microlearning themes further, expand research to high school context, and explore mobile-based microlearning.